THE EFFECT OF INTERNAL CONTROL SYSTEM, INFORMATION ASYMMETRY, SUITABILITY OF COMPENSATION AND ORGANIZATION'S ETHICAL CULTURE ON ACCOUNTING FRAUD - Halimatusyadiah Halimatusyadiah; Muhammad Hafizh Robani (UNIB Press, 2021)
This research aims to the examine the the effect of the internal control system, information asymmetry, suitability of compensation and organization's ethical culture on accounting fraud. This research was conducted at an insurance company in Bengkulu City using sampling techniques that is purposive sampling. This research uses a quantitative approach. The method to collection this data in research using primary data obtained from the result of the distribution questionnaire to accounting and finance employees at insurance companies in Bengkulu. The data were using the analyze of multiple regression with using analysisSPSS Statistic 24 program. The result from this research showing (1) the internal control system has no influence on accounting fraud. (2) information asymmetry has no influence on accounting fraud. (3) suitability of compensation has a negative influence and significant on accounting fraud. (4) organization’s ethical culture has a negative influence and significant on accounting fraud.